Acute urticaria in the infant. (24th November 2020) - Minasi, Domenico; Manti, Sara; Chiera, Fernanda; Licari, Amelia; Marseglia, Gian Luigi
Abstract: Urticaria is a mast cell‐driven disease presenting with wheals, angioedema, or both. Acute urticaria (AU) lasts < 6 weeks. AU is a not common condition in newborns and infants since they are showing an immune system functionally insufficient. In newborns and infants, AU is typically generalized and featured by large, annular, or geographic plaques, often slightly raised. The clinical features of the disease depend on the peculiar structure of neonatal and infant skin. A careful morphological examination of the lesions is essential to differentiate AU from other skin eruptions that may have overlapping features and to treat it adequately. The second‐generation antihistamines are the first‐line treatment of AU; however, only antihistamines with proven efficacy and safety should be used in newborns and infants. Corticosteroids may be added in severe cases.